A Study of the Correlation between Brain-type Natriuretic Peptide (BNP) Levels & Left Ventricular Ejection Fraction (LVEF) in Heart Failure - V. Veena; M. Ganesh; Santhi Silambanan (New Frontiers in Medicine and Medical Research Vol. 3, 2021)
Background: A significant proportion of patients diagnosed as heart failure have preserved ejection fraction. However, the differentiation between heart failure with reduced & preserved ejection fraction is difficult. The objectives of the study include: To assess the BNP levels in both patients with Heart failure with preserved LV ejection fraction and those with reduced LV ejection fraction. To study the correlation between the BNP levels and LVEF in both the groups and to ascertain whether BNP can be an useful tool in diagnosis of Heart failure with preserved LV ejection fraction]. Methods: The medical records of young patients (20–40 years) admitted during the two years 2014 & 2015 and diagnosed with Heart Failure were scrutinized in an attempt to determine the proportion of patients with preserved vs reduced ejection fraction and to assess the relationship between their Brain-type Natriuretic Peptide (BNP) levels & Left Ventricular Ejection Fraction (LVEF) in both the groups. Results: After Statistical analysis, it was found that around 36% of heart failure patients had preserved ejection fraction. There was a negative correlation between BNP levels & LVEF in both heart failure with reduced ejection fraction (HFrEF) as well as that with preserved ejection fraction (HFpEF). Majority of patients in HFpEF group were females. Mean BNP level in HFpEF group was significantly lower than that in the HFrEF group. Conclusion: Around one third of patients had Heart Failure with preserved systolic function, of which majority are females. There is a strong negative correlation between BNP levels and LVEF% in both the groups. Thus BNP levels can be used in the differentiation of HFpEF and HFrEF.